America America. - Scottish National Gallery of Modern Art, Edinburgh (Edinburgh : Scottish National Gallery of Modern Art, 1977)
de Kooning, Willem ; Olitzski, Jules ; Pollock, Jackson ; Albers, Josef ; Calder, Alexander ; Kline, Franz ; Lichtenstein, Roy ; Louis, Morris ; etc.
America America, Scottish National Gallery of Modern Art, Edinburgh, August - September 1977
boek